Tatalaksana Tinea Favosa pada Anak Usia 7 Tahun di RSUD dr. Fauziah Bireuen - Rojulan Ilham Habibi Lubis; Malahayati (Lembaga Pengembangan Kinerja Dosen, 2026)
Tinea favosa is a rare but destructive form of chronic dermatophytosis fungal infection. It is marked by the development of scutules (yellowish, cup-like crusts) and can lead to permanent cicatricial alopecia if not treated appropriately. Although its prevalence is decreasing globally, sporadic cases are still common in areas with poor sanitation. Trichophyton schoenleinii is the primary medical cause of Tinea favosa, but it can also be caused by Trichophyton violaceum or Microsporum gypseum. This report discusses a case involving a 7-year-old boy who exhibited classic clinical signs of favus. Diagnostic procedures included a physical examination, direct microscopic examination with 10-20% KOH solution, and culture on Sabouraud Dextrose Agar (SDA) to identify the fungal species. Microscopic examination revealed branching and fragmented hyphae (arthrospores) and air tunnels within the hair shaft. Culture confirmed Trichophyton schoenleinii as the primary etiologic agent. The patient was treated with oral griseofulvin combined with ketoconazole cream for 8–12 weeks. Follow-up showed resolution of the crusts and cessation of the inflammatory process, although areas of fibrosis showed permanent hair loss.